Complex networks : application for texture characterization and classification - Chalumeau, T.; da F. Costa, L.; Laligant, O.; Meriaudeau, F. (ELCVIA Electronic Letters on Computer Vision and Image Analysis, 2009)
This article describes a new method and approch of texture characterization. Using complex network representation of an image, classical and derived (hierarchical) measurements, we presente how to have good performance in texture classification. Image is represented by a complex networks : one pixel as a node. Node degree and clustering coefficient, using with traditionnal and extended hierarchical measurements, are used to characterize ”organisation” of textures.